Prevalence and factors associated with prediabetes among postpartum gestational diabetes mellitus mothers in Besut, Terengganu, 2018-2019 - Yusof, Saidah Adilah Mohamed (2021)
Background: Gestational diabetes mellitus (GDM) is a significant health issue as it causes complications during pregnancy and after delivery to both mothers and the offspring. Postpartum GDM mothers had a higher risk of progression to diabetes and prediabetes than those with normal pregnancy. Objective: The study aims to determine the prevalence of diabetes and prediabetes and factors associated with the development of prediabetes among postpartum GDM mothers in government health clinics of Besut, Terengganu in 2018-2019. Methodology: This was a cross-sectional secondary data review, conducted from January 2021 until May 2021. Data of postpartum mothers with history of GDM who performed postpartum glucose testing in government health clinics were acquired from Maternal Health Record Book KIK/1(b)/96. Descriptive and multiple logistic regression analysis were performed using IBM SPSS Statistics version 26 software. Result: A total of 429 cases were included. Most of the mothers with a history of GDM were less than 35 years old, 295 (68.8%), Malay ethnicity 427 (99.5%), married (99.8%), and achieved secondary education level, 240 (55.9%). The prevalence of diabetes and prediabetes was 2.3% (95% CI 1.6%, 3.0%) and 13.8% (95% CI 12.1%, 15.5%), respectively. Significant associations were found between previous history of GDM (Adj. OR 3.28; 95% CI 1.83, 5.87; p < 0.001) and insulin usage (Adj. OR 2.75; 95% CI 1.51, 4.99; p= 0.001) with development of prediabetes at postpartum period. Conclusion: The prevalence of diabetes and prediabetes among postpartum GDM mothers in Besut district was as high as other studies in Malaysia and globally. Women with a previous history of GDM and insulin usage should be focused on prevention strategies as they were at higher risk of developing prediabetes in the postpartum period.